Establishing correlation among optical, electrical and photon interaction parameters for ZnxTe100−x (x = 5, 20, 30, 40, 50) alloys. (13th March 2019) - Singh, Harinder; Sharma, Jeewan; Singh, Tejbir
Abstract: An attempt has been made to establish correlation among optical, electrical and photon interaction parameters for some ZnTe binary alloys. Conventional melt quenching technique is used to prepare Znx Te100-x (x = 5, 20, 30, 40, 50) alloys. The thin films on cleaned glass substrates were deposited using thermal evaporation technique. Optical, electrical and photon interaction parameters in terms of band gap energy (Eg ), carrier concentration (n), effective atomic number (Zeff ) and electron density (Ne ) has been obtained for all the alloy compositions. A non-linear correlation has been observed between Eg and Zeff of the alloy samples. The carrier concentration (n) decreases with the decrease in Te atoms, whereas electron density increases with the increase in Zn atoms.